2016
DOI: 10.1002/syn.21894
|View full text |Cite
|
Sign up to set email alerts
|

Subtle alterations of excitatory transmission are linked to presynaptic changes in the hippocampus of PINK1‐deficient mice

Abstract: Homozygous or heterozygous mutations in the PTEN-induced kinase 1 (PINK1) gene have been linked to early-onset Parkinson's disease (PD). Several neurophysiological studies have demonstrated alterations in striatal synaptic plasticity along with impaired dopamine release in PINK1-deficient mice. Using electrophysiological methods, here we show that PINK1 loss of function causes a progressive increase of spontaneous glutamate-mediated synaptic events in the hippocampus, without influencing long-term potentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
5
9
0
Order By: Relevance
“…Mildly significant was the enrichment of 21 factors of the “Dopaminergic synapse” pathway ( q value 0.005), 16 factors of the “GABAergic synapse” pathway ( q value 0.008), and 18 factors of the “Glutamatergic pathway” pathway ( q value 0.015). These data are in excellent consistency with previously established roles of PINK1 as a component of MAPK signaling [ 51 , 52 ], as an activator of PARKIN which prevents bacterial invasions [ 18 ], and as a modifier of dopaminergic, GABAergic, and glutamatergic signaling in the nigrostriatal pathway [ 44 , 53 56 ]. The agreement of our bioinformatics analysis of the global transcriptome with previously published cell biology data provides credibility to this automated approach.…”
Section: Resultssupporting
confidence: 87%
“…Mildly significant was the enrichment of 21 factors of the “Dopaminergic synapse” pathway ( q value 0.005), 16 factors of the “GABAergic synapse” pathway ( q value 0.008), and 18 factors of the “Glutamatergic pathway” pathway ( q value 0.015). These data are in excellent consistency with previously established roles of PINK1 as a component of MAPK signaling [ 51 , 52 ], as an activator of PARKIN which prevents bacterial invasions [ 18 ], and as a modifier of dopaminergic, GABAergic, and glutamatergic signaling in the nigrostriatal pathway [ 44 , 53 56 ]. The agreement of our bioinformatics analysis of the global transcriptome with previously published cell biology data provides credibility to this automated approach.…”
Section: Resultssupporting
confidence: 87%
“…Because other factors, in particular exercise and stress hormone levels, are known to affect neurogenesis, we studied whether loss of PINK1 caused changes in home cage activity and corticosterone levels of mice; however, neither was the case, which ruled out that decreased physical activity and/or increased stress hormone levels, in part, were responsible for neurogenesis defects of PINK1 2/2 mice. We cannot entirely exclude that a subtle change in excitatory neurotransmission in the hippocampus of PINK1 2/2 mice (61) may have influenced neurogenesis in our studies; however, we note that the reported alterations in glutamate release were without effect on hippocampal long-term potentiation (61), which was in agreement with a previous work that showed normal basal neurotransmission and synaptic plasticity in the hippocampus of PINK1 2/2 mice (62). In addition to exogenous factors, ROS affect neurogenesis and are implicated in the pathogenesis of many neurodegenerative disorders, including PD and Alzheimer's disease (63,64).…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondrial activity is important for energy supply in neurons, and mitochondrial dysfunctions is thought to lead to neurodegenerative diseases, including Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS). These are intractable disorders characterized by irreversible loss of neurons (Devine & Kittler, 2018;Feligioni et al, 2016;Islam, 2017;Smith, Shaw, & De Vos, 2017). Despite their differences in pathophysiological features and cell-types specificities, impairment of energy metabolism associated with mitochondrial failure is often observed in these diseases, e.g., dysfunctions of NADH-ubiquinone reductase (also called as mitochondrial complex I) in PD (Schapira et al, 1989), and succinate dehydrogenase (mitochondrial complex II) in HD (Miller & Zaborszky, 1997), and axonal transport of mitochondria in ALS (Moller, Bauer, Cohen, Webster, & Vos, 2017).…”
Section: Introductionmentioning
confidence: 99%